Senegal Dairy Value Chain Nutrition Data - International Food Policy Research Institute; GRET; Université Gaston Berger; Cellule de Lutte contre la Malnutrition (International Food Policy Research Institute, 2017)
IFPRI in collaboration with the Laiterie du Berger (milk factory in Richard Toll, Senegal), the GRET (international NGO), University Gaston Berger (UGB) in Saint Louis, Senegal and the Cellule de Lutte contre la Malnutrition (CLM) conducted an impact evaluation of a dairy value chain program in Senegal. The aim of the study was to assess if a dairy value chain could be used to distribute a micronutrient-fortified yoghurt (MNFY), to improve hemoglobin concentration and decrease anemia prevalence among preschool children at the individual level, in a remote area in Northern Senegal. Delivery of the MNFY was conditional on regular delivery of milk to the dairy cooperative supplying the MNFY and collecting milk from milk producing households. A cluster randomized control trial was used to compare children 24 to 59 months of age at baseline from households who received the MNFY coupled to a behavior change communication campaign (BCC) focusing on anemia prevention, to children from a control group (receiving BCC only) after one year. Randomization was at the level of the family concession (households from extended family). Households eligible were those having a child of the target age at baseline and willing to deliver milk to the dairy factory. The intervention started in February 2013 and lasted one year. A baseline survey was conducted in January 2013, two follow-up surveys in April and September 2013 and an endline survey in January 2014. Data were collected with questionnaires at the household, maternal and child level, during the baseline and endline surveys. The household questionnaire collected household-level information on socioeconomic characteristics, household composition and on household food insecurity. The mother questionnaire collected individual-level information on education, nutrition and health knowledge and maternal hemoglobin concentration. Hemoglobin levels for selected children in the household were collected longitudinally at baseline, follow-up surveys and at endline.